Microcausality and Quantization of the Fermionic Myers-Pospelov Model - Lopez-Sarrion, J (Springer New York LLC, 2012)
We study the fermionic sector of the Myers and Pospelov theory with a general background n. The spacelike case without temporal component is well defined and no new ingredients came about, apart from the explicit Lorentz invariance violation. The lightlike case is ill defined and physically discarded. However, the other case where a nonvanishing temporal component of the background is present, the theory is physically consistent. We show that new modes appear as a consequence of higher time derivatives. We quantize the timelike theory and calculate the microcausality violation which turns out to occur near the light cone. © 2012 Springer-Verlag / Società Italiana di Fisica.